Higher efficiency of the liver phosphorylative system in diabetic Goto-Kakizaki (GK) rats - Palmeira, Carlos M. (1999)
Liver mitochondrial bioenergetics of Goto-Kakizaki (GK) rats (a model of non-insulin dependent diabetes mellitus) reveals a [Delta][Psi] upon energization with succinate significantly increased relatively to control animals. The repolarization rate following ADP phosphorylation is also significantly increased in GK mitochondria in parallel with increased ATPase activity. The increase in the repolarization rate and ATPase activity is presumably related to an improved efficiency of F0F1-ATPase, either from a better phosphorylative energy coupling or as a consequence of an enlarged number of catalytic units. Titrations with oligomycin indicate that diabetic GK liver mitochondria require excess oligomycin pulses to completely abolish phosphorylation, relative to control mitochondria. Therefore, accepting that the number of operational ATP synthase units is inversely proportional to the amount of added oligomycin, it is concluded that liver mitochondria of diabetic GK rats are provided with extra catalytic units relative to control mitochondria of normal rats. Other tissues (kidney, brain and skeletal muscle) were evaluated for the same bioenergetic parameters, confirming that this feature is exclusive to liver from diabetic GK rats.